A metatheoretical framework for organizational wellbeing research: Toward conceptual pluralism in the wellbeing debate. (May 2023) - Kenttä, Peter; Virtaharju, Jouni
The organizational wellbeing discourse has in the past decades gravitated toward two adversarial camps. The first camp draws increasingly from positive psychology and studies wellbeing as the presence of positive attributes centered around the individual. The second camp is critical toward the first one from a sociological standpoint by warning about its hidden tyranny and detrimental organizational consequences. In this paper we interrogate the conceptual foundations of the two camps and argue that the paradigmatic divide between them can be traced to their antithetical assumptions about the nature of human freedom. To move beyond the paradigmatic standstill, we suggest adopting Kenneth Burke's dramatistic pentad as a metatheoretical framework for organizational wellbeing research. The pentad can help integrate concerns and viewpoints from both camps and facilitate the exploration of novel opportunities to conceptualize wellbeing in organizations. The proposed metatheoretical framework acknowledges the plural and essentially contested character of wellbeing whilst promoting theoretical pluralism in organizational wellbeing research. We also illustrate the use of the dramatistic pentad through three thought-provoking conceptualizations of organizational wellbeing. The illustrations show how the dramatistic pentad can be used to spur much needed conceptual imagination within organizational wellbeing research.